1997
DOI: 10.1002/(sici)1096-9896(199709)183:1<39::aid-path1088>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

The association between tumour progression and vascularity in the oral mucosa

Abstract: Tumourigenesis in experimental models is associated with the formation of new blood vessels (angiogenesis). Recent studies have suggested that tumour angiogenic activity may be inferred in histological sections by measuring the density of the vasculature. The purpose of this study was to determine whether the transition from normal to dysplastic and neoplastic tissue in the oral mucosa is accompanied by quantitative or qualitative changes in the vascularity of the tissue, and how the estimate of vascularity is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
67
1
1

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(78 citation statements)
references
References 18 publications
9
67
1
1
Order By: Relevance
“…High microvessel density was associated with metastasis and/or a worse clinical outcome in many studies (Shpitzer et al 1996;Pazouki et al 1997;Penfold et al 1996;Williams et al 1994), but this observation was not confirmed in several other studies (Dray et al 1995;Gleich et al 1996;Janot et al 1996;Moriyama et al 1997). Our results suggest a correlation of MVD with clinical stage.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…High microvessel density was associated with metastasis and/or a worse clinical outcome in many studies (Shpitzer et al 1996;Pazouki et al 1997;Penfold et al 1996;Williams et al 1994), but this observation was not confirmed in several other studies (Dray et al 1995;Gleich et al 1996;Janot et al 1996;Moriyama et al 1997). Our results suggest a correlation of MVD with clinical stage.…”
Section: Discussioncontrasting
confidence: 83%
“…Studies examining the association of VEGF immunohistochemical expression and tumor angiogenesis with clinicopathological factors and outcome in head and neck squamous cell carcinoma (HNSCC) have yielded inconclusive and conflicting results (Leedy et al 1994;Dray et al 1995;Gleich et al 1996;Shpitzer et al 1996;Pazouki et al 1997;Penfold et al 1996;Salven et al 1997;Maeda et al 1998;Neuchrist et al 1999;Smith et al 2000;Aebersold et al 2000;Gallo et al 2001;Mineta et al 2002;Dunphy et al 2002). These discrepancies may be caused by differences in tumor location, the choice of antibodies, and cutoffs as well as variability in IHC protocols (Vermeulen et al 2002;Hannen et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of studies evaluating the prognostic significance of microvessel density in head and neck squamous cell carcinoma [1,15,23,24,32,37] with conflicting and contradictory results. In all of these reports, investigators used pan-endothelial markers, namely, CD34, CD31, and von Willebrand factor, to highlight microvessels.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis, the formation of new blood vessels, is crucial to the growth, invasion and metastasis of a tumour 6,8 . A significant increase in vascularity occurs during the transition from normal oral mucosa (NOM), through differing degrees of dysplasia, to invasive squamous cell carcinoma (SCC) 2,12,17 . This increase in vascularity has been associated with tumour progression from early to late carcinoma 17 and lymph node metastasis 18 .…”
mentioning
confidence: 99%
“…A significant increase in vascularity occurs during the transition from normal oral mucosa (NOM), through differing degrees of dysplasia, to invasive squamous cell carcinoma (SCC) 2,12,17 . This increase in vascularity has been associated with tumour progression from early to late carcinoma 17 and lymph node metastasis 18 . Previous research has shown that an adequate blood supply is essential for solid tumour growth and metastasis 7 .…”
mentioning
confidence: 99%